Antioxidant and Hypolipidemic Effect of Plumeria Rubra L. in Alloxan Induced Hyperglycemic Rats - A. John Merina; D. Sivanesan; V. Hazeena Begum; N. Sulochana (E-Journal of Chemistry)
Antioxidant and hypolipidemic activity of the flovone glycoside isolated from Plumeria rubra L. was carried in alloxan induced hyperglycemic rats. The flavonoid treatment produced a significant reduction in the level of serum triglycerides, while there was no reduction in the serum cholesterol and glucose. Antioxidant activity of the drug was also confirmed through in vitro studies.